1990
DOI: 10.1128/jvi.64.4.1756-1763.1990
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of elements within the SL3-3 virus enhancer for T-cell specificity

Abstract: Elements within the enhancer of T-lymphomagenic SL3-3 virus were examined for their contributions to transcriptional activity in T lymphocytes and non-T cells. A region containing two sequences homologous to the enhancer core consensus sequence and a sequence homologous to the binding site for factor LVb was found to have the largest effect on activity. Evidence was obtained that suggests that the activity of this region was greater in T lymphocytes than in non-T cells and that multiple elements within it were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Mutation of either a c-Myb-or CBF-binding site inhibited the activity of the TCR␦ and TCR␥ enhancers in T cells (36,39). Mutation of the c-Myb-or CBF-binding sites inhibited the activity of the SL3 enhancer in T cells (6,34,54,55,64,94,106). The cotransfection experiments presented here are important because they explicitly show that c-Myb and CBF␣2-451 are capable of driving transcription through these sites.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Mutation of either a c-Myb-or CBF-binding site inhibited the activity of the TCR␦ and TCR␥ enhancers in T cells (36,39). Mutation of the c-Myb-or CBF-binding sites inhibited the activity of the SL3 enhancer in T cells (6,34,54,55,64,94,106). The cotransfection experiments presented here are important because they explicitly show that c-Myb and CBF␣2-451 are capable of driving transcription through these sites.…”
Section: Discussionmentioning
confidence: 78%
“…In all cases, identical mutations were simultaneously generated in each of the 72-bp repeats of the SL3 enhancer. Mutations in each of the three binding sites as well as in core I were previously found to inhibit the transcriptional activity of the SL3 LTR in T lymphocytes (6,34,54,55,64,94,106). In addition, mutation of the Myb site was found to nearly eliminate the lymphomagenicity of SL3 (66).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The exact mecha-nisms by which virus enhancer structures determine disease induction are not known. First, the enhancer effect on provirus transcription may determine the level of expression of a viral gene product in the target cell or the virus load in target tissues (17,27). However, in the case of thymic lymphomagenesis it was found that infection of target tissue is not sufficient for subsequent disease development (11,12).…”
mentioning
confidence: 99%